Effects of sodium sulfate and sodium chloride for sonochemical degradation on1,4-benzoquinone and hydroquinone in aqueous solution - Uddin, Md. Helal; Okitsu, Kenji (Penerbit Universiti Kebangsaan Malaysia, 2018)
1,4-benzoquinone, with the molecular formula C6H4O2, is generally known as a para-quinone. It is a six-member ring compound with an oxidized derivative known as 1,4-hydroquinone, which is a bright yellow crystal that has an irritating odour. On the other hand, hydroquinone, also known as benzene-1,4-diol, has the chemical formula C6H4(OH)2. It looks like a white granular solid. Quinone is generally used as a precursor to hydroquinone. The skeletal muscle relaxant, ganglion blocking agent, benzoquinonium, is made from benzoquinone. It is utilized to suppress double-bond migrations during olefin metathesis reactions. 1,4-benzoquinone is also used in the synthesis of Bromodol, while hydroquinone is the main ingredient in black-and-white photographic developers such as film and paper developers, where it diminishes the silver halide to elemental silver. There are various other uses related to this diminishing power. As a polymerization inhibitor, hydroquinone prevents the polymerization of methyl methacrylate, acrylic acid, etc. Studies have demonstrated the various effects of Na2SO4 and NaCl on the sonochemical degradation of 1,4-benzoquinone and hydroquinone using a 200-kHz sonicator. The highest degradation rate was obtained in the presence of 0.433 M Na2SO4 for 1,4-benzoquinone. After 30 minutes of ultrasonic irradiation, the total concentration of 1,4-benzoquinone decreased to 99% in the presence 0.433 M Na2SO4. Without Na2SO4, the sonochemical degradation rate of 1,4-benzoquinone was 4.5 times higher than that of hydroquinone, whereas in the presence of 0.433 M Na2SO4 under the same conditions the initial reaction rate of 1,4-benzoquinone was increased to become 10.6 times higher than that of hydroquinone. On the other hand, in the presence of NaCl, no effects were observed for the decomposition of hydroquinone but negative effects were clearly observed for the decomposition of 1,4-benzoquinone.